Optimization of Channel Length Nano-Scale Sinwt Based Sram Cell - Naif, Yasir Hashim; Alsibai, Mohammad Hayyan; Abdul Manap, Sulastri (EDP Sciences, 2015)
This paper represents a channel length ratio optimization at a different high logic level voltage for 6-Silicon Nanowire Transistors (SiNWT) SRAM cell. This study is the first to demonstrate an optimized length ratio of nanowires with different Vdd of nano-scale SiNWT based SRAM cell. Noise margins (NM) and inflection voltage (Vinf) of transfer characteristics are used as limiting factors in this optimization. Results indicate that optimization depends on both length ratios of nanowires and logic voltage level (Vdd), and increasing of high logic voltage level of the SiNWT based SRAM cell tends to decrease in the optimized nanowires length ratio with decreasing in current and power.